Business model for cross-border interconnections in the Mediterranean basin - Poudineh, R; Rubino, A (Oxford Institute for Energy Studies, 2016)
The complementarity between electricity systems of the north and south Mediterranean basin along with the need for diversification of energy resources and optimisation of energy systems are among the reasons for greater electricity trade and cross-border integration in the region. However, development of cross-border interconnection in the Mediterranean basin requires a business model which provides incentives for investment and efficient operation, manages risks and uncertainties and facilitates coordinated planning and governance. We contend that, due to high perceived risk of investment, delivery of interconnection projects through the EU regulated model is less likely, or only possible at prohibitively high rate of returns. The merchant transmission initiative (MTI), on the other hand, is seen as an exception under the EU laws and can be approved only if the project meets a set of strict conditions. We, therefore, advocate a hybrid business model in which the main benefits of a merchant model are maintained within a regulated structure. We highlight the main components of the proposed business model and show how it addresses the key features of a viable business model in relation to incentives, risks and governance. Our analysis demonstrates that the proposed Mediterranean business model for interconnection can better provide incentives for investment and is more compatible with the region’s energy scenario, governance structure and the risk attitude.